An analysis of involvement of HCI experts in distributed software development - Cetin, Gorkem; Verzulli, Damiano; Frings, Sandra (Springer-Verlag Berlin, 2007)
Traditionally, free and open source software (F/OSS) developers have focused more on the features of a specific application, most of the time ignoring the necessity of user-centric design. This has mainly stemmed from the fact that developers have little interaction with HCI studies, knowledge bases and reports. Moreover, the lack of user interface designers has resulted in a lack of awareness of this area. As a consequence, the user centric design phenomenon within F/OSS applications has been neglected. In this paper, we have mentioned various problems that would slow down a ROSS project development towards a user-engineered software, and investigated the ways that HCI experts and developers interact with each other and researched bug reporting systems by means of eligibility to issue usability bugs. For the conclusion part, we have explored possible ways to achieve a user-centric design in a project with asynchronous interaction among geographically distributed developers.
2nd International Conference on Online Communities and Social Computing held at the HCI International 2007 -- JUL 22-27, 2007 -- Beijing, PEOPLES R CHINA
Keywords: F/OSS; HCI; usability; open source; distributed usability; user centric design